2008
DOI: 10.13057/biodiv/d090413
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior of macaques, Macaca fascicularis (Raffles, 1821) on tourists at Kaliurang nature recreation forest, Yogyakarta

Abstract: Research was conducted in Kaliurang nature recreation forest area, in Gunung Merapi National Park, Yogyakarta. The research aim to investigate the proportion of aggressive behavior of monkeys [Macaca fascicularis (Raffles, 1821)] to tourists. Direct observation method was used to observe the monkeys behavior in the interaction to the tourists. And questioners were distributed to the tourists to know expectation of the tourists which related to the existence of the monkeys in that conservation area. Analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on age, AG 1 aggressive behaviour is mainly done by adult male monkeys (10 times) and followed by adult female monkeys (once). Previous aggressiveness studies by Djuwantoko et al [13], Pramesthy [14], and Teguh [15] reported that adult male monkeys are the most aggressive in behaviour compared to other age and sex groups. Monkey's aggressive behaviour towards visitors is usually done by stealing food, grinning, and intimidating with a potential attack.…”
Section: Resultsmentioning
confidence: 99%
“…Based on age, AG 1 aggressive behaviour is mainly done by adult male monkeys (10 times) and followed by adult female monkeys (once). Previous aggressiveness studies by Djuwantoko et al [13], Pramesthy [14], and Teguh [15] reported that adult male monkeys are the most aggressive in behaviour compared to other age and sex groups. Monkey's aggressive behaviour towards visitors is usually done by stealing food, grinning, and intimidating with a potential attack.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, other macaques welcome visitors by following them and ignoring them until visitors leave the location. According to Djuwantoko et al [46], mitigating the HPC must reduce the number of visitors. As well as adult male is the most aggressive individual that commonly threatens male-visitor.…”
Section: Results Findingsmentioning
confidence: 99%
“…Human conflict is possible with these three types of animals, especially the long-tailed macaque. Several studies have discussed long-tailed macaque conflicts with humans in the Mount Merapi landscape [98]. However, human conflict with leopard cats and barking deer have not occurred.…”
Section: Discussionmentioning
confidence: 99%